The Implementation of Quizlet to Learn Vocabulary Towards Junior High School Students - Dewi, Ni Putu Adis Cantika (Universitas Suryakancana, 2023)
Â Â ABSTRACTTechnology in Education has been developing these centuries. Thanks to the evolution of technology and education, there are many method and aproachment of learning methods that are facilitated by technology. The innovation and creativity is needed when it comes to meet the learning goals using technologies. Learners and tutors has used many applications that support learning process, one of them is Quizlet. Quizlet was founded by Andrew Sutherland in 2005. It is well-known application that shifting into modern quiz and flashcards to learn vocabulary. It is completed with four types of quizzes and the interface of the applications had been made easier for beginners. It is known that students utilize applications in their learning process. In this paper, it will discussed on how the implementation of quizlet to learn one specific skill, that is vocabulary and how tutors and teachers engaging the features of quizlet and authorize it. Through the data collected, writers wats to know whether quizlet can be utilize in learning vocabulary.Keyword: Quizlet, Vocabulary, Application, IDT